Prevalence of Vitality in Fixed Partial Denture Done by the Undergraduates - A Retrospective Study - Tulsani Minal Gopal1 , Subhashree. R2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Fixed partial denture is any dental prosthesis that is luted, screwed, or mechanically attached or otherwisesecurely retained to natural teeth, tooth roots, and/or dental implants/abutments that furnish the primarysupport for the dental prosthesis and restoring teeth in a partially edentulous arch; it cannot be removed bythe patient. This study is aimed to evaluate prevalence of vitality of pulp before and after tooth preparationdone by undergraduates for fixed partial denture. A retrospective study was done in which 955 teeth wereprepared for fixed partial denture from 1 June 2019 till 1 March 2020 were included. Data was reviewedfrom the patients records of 86,000 patients documented in a private institution. Statistical analysis wasperformed to assess the vitality of pulp before and after tooth preparation done by undergraduates for fixedpartial denture. There was a statistically significant difference when postoperative vitality was compared indifferent age groups (p<0.05). Out of 200 abutments that were non vital postoperatively only 48% of theabutment had indication for endodontic therapy. Lack of experience of dental students can be the reason forpulpal exposure during preparation. It might be difficult for students to get the parallelism of the abutmentsmainly in the multiunit fixed dental prosthesis. Treatment planning should be done carefully along with thestudents and a beforehand mock preparation should be done on plaster models instead of direct preparationof the vital abutments, this can also help students to perform different types of treatments adequately.